Metabolomics and gut microbiota analysis reveal the differential efficacy of areca nut and charred areca nut in treating constipation - Wang, Li-sha; Wu, Jiao-xia; Zhang, Fang; Huang, Yan; Jiang, Yue-xia; Li, Yong-hui (Frontiers in Nutrition, 2024)
Background: Areca nut (AN) is a traditional Chinese herbal medicine used for centuries to treat gastrointestinal (GI) disorders. Charred AN (CAN) is a processed product of AN with similar therapeutic effects. This study aimed to investigate the therapeutic mechanisms of AN and CAN for constipation via metabolomics and gut microbiota analysis. Methods: In this study, the rats were randomly divided into 5 groups (n = 6): control, constipation model, positive drug, AN treatment, and CAN treatment groups. Constipation was induced by intragastric administration of loperamide hydrochloride, followed by 14-day treatment with mosapride, AN, or CAN. The efficacy difference between AN and CAN was assessed by evaluating the weight gain, fecal water content, GI transit rate, colonic histopathology, serum levels of GI hormones, gut microbiota, and fecal metabolites. Results: The results demonstrated that both AN and CAN could alleviate loperamide-induced constipation. Furthermore, they significantly elevated the serum levels of motilin, vasoactive intestinal peptide, substance P, and acetylcholine. 16S rRNA analysis revealed that AN regulated the relative abundance of Bacillus, UCG-005, norank_f__Muribaculaceae, Candidatus_Saccharimonas, and Ruminococcus, whereas CAN modulate the relative abundance of Lactobacillus, Bacillus, norank_f__Muribaculaceae, Ruminococcus, unclassified_f__Oscillospiraceae, and unclassified_f__Prevotellaceae. Moreover, the metabolic profile of AN- and CAN-treated rats was also different, where AN treatment involved pathways of citrate cycle (TCA) and tyrosine, alanine, aspartate, and glutamate metabolisms. Whereas CAN treatment involved pathways of steroid and primary bile acid biosynthesis, as well as pyrimidine and purine metabolisms. Pearson correlation analysis indicated a close relationship between gut microbiota and fecal metabolites. Conclusion: In summary, this study revealed that AN may protect GI mucosa, enhance GI motility, and alleviate constipation symptoms by regulating the relative abundance of specific gut microbiota (Bacillus, UCG-005, norank_f__Muribaculaceae, Candidatus_Saccharimonas, Ruminococcus) as well as citrate cycle or tyrosine, alanine, aspartate, and glutamate metabolic pathways. Furthermore, CAN was observed to promote gastric emptying and intestinal propulsion, thereby alleviating constipation, by modulating the relative abundance of specific gut microbiota (Lactobacillus, Bacillus, norank_f__Muribaculaceae, Ruminococcus, unclassified_f__Oscillospiraceae, unclassified_f__Prevotellaceae) as well as steroid and primary bile acid biosynthesis, as well as pyrimidine and purine metabolic pathways.